2020
DOI: 10.3390/insects11020121
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of DNA Methyltransferases 1 (DNMT1) in Regulating Sexual Dimorphism in the Cotton Mealybug, Phenacoccus solenopsis

Abstract: The cotton mealybug, Phenacoccus solenopsis, is an invasive pest that can cause massive damage to many host plants of agricultural importance. P. solenopsis is highly polyphagous, and shows extreme sexual dimorphism between males and females. The functions of DNA methyltransferase (DNMT) enzymes in the cotton mealybug have not been well studied. Here, we carried out an investigation of DNMTs in cotton mealybug to study their roles in sexual dimorphism. We found that the cotton mealybug has two copies of PsDnmt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Both dsRNAs showed satisfactory RNAi efficiency (Fig. 4a ), similar to those obtained via other RNAi methods used in the cotton mealybug, such as siRNA microinjection 52 and direct dsRNA feeding 53 . Meanwhile, shared phenotypes produced by the two molecules further proved the same on-target effects for both of them.…”
Section: Discussionsupporting
confidence: 73%
“…Both dsRNAs showed satisfactory RNAi efficiency (Fig. 4a ), similar to those obtained via other RNAi methods used in the cotton mealybug, such as siRNA microinjection 52 and direct dsRNA feeding 53 . Meanwhile, shared phenotypes produced by the two molecules further proved the same on-target effects for both of them.…”
Section: Discussionsupporting
confidence: 73%
“…It is also suggested that DNA methylation may have a role in the recognition and silencing of paternally derived chromosomes in males in the process of PGE (Bongiorni et al, 1999; Buglia et al, 1999). Supporting the idea that DNA methylation may be involved in sexual dimorphism and PGE in mealybugs and other scale insects, two recent studies have identified sex‐biased expression of the DNA methyltransferase DNMT1 in adult Phenacoccus solenopsis (Omar et al, 2020) and Ericerus pela (Yang et al, 2015), with females showing considerably higher expression compared to males in both species.…”
Section: Introductionmentioning
confidence: 87%
“…Supporting the idea that DNA methylation may be involved in sexual dimorphism and PGE in mealybugs and other scale insects, two recent studies have identified sex-biased expression of the DNA methyltransferase DNMT1 in adult Phenacoccus solenopsis (Omar et al, 2020) and Ericerus pela (Yang et al, 2015), with females showing considerably higher expression compared to males in both species.…”
mentioning
confidence: 87%
“…In our FAW DNA methylation map, the mCs were detected in CG, CHG, and CHH (H represents A, T, or G) contexts. The DNA methyltransferases 3 (DNMT3) catalyzes non-CG context methylation, but DNMT3 is lost in Lepidoptera, and CHH context methylation is not observed in Lepidoptera (Glastad et al, 2011;Omar et al, 2020). However, CHH methylation was identi ed in Bombyx mori (Lepidoptera:Bombycidae), albeit in an extremely small proportion (Li et al, 2020), and in the absence of DNMT3 (Gao et al, 2020).…”
Section: Characteristics Of Faw Dna Methylation Mapmentioning
confidence: 99%